Role of Investment, Inflation and Unemployment on Tax Collection of Pakistan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The major development variables was checked by the effects of taxation by using linear regression, and looking at the results and their discussions it is very clearly observed by the researchers that increased tax collection will boost the inflation, means producers are shifting the burden of taxes on the consumers which is not a good sign for the smooth economic system, and tax collections are not purely concerned with the investment means investors are not looking for the tax shelter or rebate but only they are looking to the opportunities, and finally tax collection have negative impact on Un-employment rate, which states that improved tax collections are properly utilized in productive opportunities in the result un-employment rate is decreasing.